Memory Loss and Scenic Experience: An Arts Based Investigation - Jill Bennett (Forum: Qualitative Social Research, 2019)
In our research, two groups of people living with memory loss due to mid-stage dementia were invited to view a film installation, centred on the experience of a woman with a brain lesion and dense amnesia. The groups, recruited from day-care and support settings, were living at home. One included informal care-givers. After the film, each participated in a visual matrix: A group-based method of eliciting image-led and affective associations in response to aesthetic stimuli to support shared and distributed memory. We hypothesised that the associative process of the visual matrix would support meaningful engagement for participants with dementia.